Effectiveness of Fewer Falls, an online group-based self-management fall prevention programme for people with multiple sclerosis: protocol of a randomised controlled trial - Maria Flink; Charlotte Ytterberg; Kristina Gottberg; Marie Kierkegaard; Susanna Tuvemo Johnson; Elizabeth Walker Peterson; Ulrika Meijer; Johanna Bylinder (BMJ Open)
Introduction Fewer Falls is a manualised self-management fall prevention programme co-developed for and with ambulatory and non-ambulatory people with multiple sclerosis (PwMS). Findings from a feasibility study indicate the necessity of a full-scale randomised controlled trial (RCT).Methods and analysis A parallel-group RCT with a mixed methods process evaluation as well as a cost-effectiveness evaluation will be conducted. We aim to recruit 240 PwMS, who will be stratified by ambulation level and randomised 1:1 in blocks of eight to intervention or control. The group-based self-management fall prevention intervention involves eight 2-hour online synchronous sessions (approximately eight participants/group) facilitated by a licensed healthcare professional and home assignments to be completed by participants between sessions. The setting is online, and participants can be located anywhere in Sweden. The control and intervention groups will also receive a brochure on fall risk factors and fall prevention in addition to their standard MS care and rehabilitation. Data collection will be performed at baseline and 3, 6 and 12 months after the start of the intervention. Falls will be monitored via a short message service every week during 1 year from the start of the intervention. The primary outcome is fall frequency (falls/person/year). Secondary outcomes include injurious falls, falls control, fear of falling, falls self-efficacy, activity curtailment, perceived effect of MS, self-rated health and cost-effectiveness.Ethics and dissemination Ethical approval has been obtained from the Swedish Ethical Review Authority (registration numbers 2022-06667-01 and 2023-07723-02). The RCT will adhere to the Declaration of Helsinki. Written consent to participate will be obtained from all participants. Study-related information about participants will be stored securely at Karolinska Institutet. The results will be presented in peer-reviewed journals, through the patient organisation Neuro Sweden, at conferences, and in social media.Trial registration number ClinicalTrials.gov, NCT05789225.